\(\displaystyle 9\,o = 15\,o + 15 - 3\)

\(\displaystyle 9(\dfrac{1}{9}),o = 15(\dfrac{1}{9})\,o + 12(\dfrac{1}{9})\)

\(\displaystyle o = \dfrac{15}{9}\,o + \dfrac{12}{9}\)

\(\displaystyle o - \dfrac{15}{9}\,o = \dfrac{15}{9}\,o - \dfrac{15}{9}\,o + \dfrac{12}{9} \)

\(\displaystyle -\dfrac{2}{3}\,o = \dfrac{12}{9}\)

\(\displaystyle -\dfrac{2}{3}(-\dfrac{3}{2})\,o = \dfrac{12}{9}(-\dfrac{3}{2})\)

\(\displaystyle o = \dfrac{12}{9}(-\dfrac{3}{2})\)

\(\displaystyle o = -2\)

Check:

\(\displaystyle 9(-2) = 15(-2) + 15 - 3\)

\(\displaystyle -18 = -18\)

Yes.

Find A

\(\displaystyle -\dfrac{10}{7}\,a = 13\,a + 99 - 1\)

\(\displaystyle 9(\dfrac{1}{9}),o = 15(\dfrac{1}{9})\,o + 12(\dfrac{1}{9})\)

\(\displaystyle o = \dfrac{15}{9}\,o + \dfrac{12}{9}\)

\(\displaystyle o - \dfrac{15}{9}\,o = \dfrac{15}{9}\,o - \dfrac{15}{9}\,o + \dfrac{12}{9} \)

\(\displaystyle -\dfrac{2}{3}\,o = \dfrac{12}{9}\)

\(\displaystyle -\dfrac{2}{3}(-\dfrac{3}{2})\,o = \dfrac{12}{9}(-\dfrac{3}{2})\)

\(\displaystyle o = \dfrac{12}{9}(-\dfrac{3}{2})\)

\(\displaystyle o = -2\)

Check:

\(\displaystyle 9(-2) = 15(-2) + 15 - 3\)

\(\displaystyle -18 = -18\)

Yes.

__Your Turn__Find A

\(\displaystyle -\dfrac{10}{7}\,a = 13\,a + 99 - 1\)

Last edited: